Self Efficacy students in integrated thematic learning in class IV SDN trial Padang City: Self Efficacy Siswa Dalam Pembelajaran Tematik Terpadu di Kelas IV SDN Percobaan Kota Padang - Yulia Darniyanti (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
This study to describe the Self Efficacy, students who have verygood Self efficacy, This study is a qualitative research with descriptive research. The subjects were IV.B classroom teachers, students, and parents. The object of this research is Self Efficacy students in an integrated thematic learning. Data were analyzed using data reduction, data display, and conclusion.The results of this study indicate that students who have very good Self Efficacy are always active in the learning process, always getting support and motivation from teacher, Friend and parents. Old people complete the facilities. Children to learn, from Self Efficacy. They are also active in the classroom; always get support and motivation from the teacher old friends and parents. Students complete the facility and provide tutoring study. Students who have low or not good Self Efficacy have never been active in the class room, they not get support and and motivation from teacher, friends and parents. Their learning facilities cannot be fully met bay parents. They do not provide additional tutoring because economy.